SPEECH STYLES USED BY YOUNG FEMALE AND MALE TEACHERS IN TEACHING ENGLISH TO THEIR OLDER STUDENTS - Febriani N Ronsumbre; Esther H Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study discussed about the speech styles used by a young female and a young male teacher in teaching English to their older students, the tendencies of using the features of each speech styles, and the use of opposite gendered speech styles. Through the classroom observation, the findings showed that the young female teacher applied six features of female speech styles and five features of male speech styles while the findings of theyoung male teacher showed that he only applied five features of male speech styles and applied six features of female speech styles.From the findings, it could be concluded that the most dominant speech styles used by the young female teacher is ‘Female Speech Style’ and the most dominant feature is ‘Co-operative’. And, the most dominant speech styles used by the young male teacher is ‘Male Speech Style’ and the most dominant feature is ‘Co-operative’ feature of female speech style